2021
DOI: 10.2147/copd.s294217
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Inhaled Corticosteroids in Patients with COPD – A Prospective Observational Study

Abstract: Background Inhaled corticosteroids (ICS) are widely used in the treatment of chronic obstructive pulmonary disease (COPD), but recent studies have raised doubts whether all COPD patients will benefit from ICS. This study evaluates in a real-life setting the effects of ICS withdrawal in patients with COPD. Methods The study was a prospective intervention study following patients with COPD for 6 months after abrupt withdrawal of ICS. FEV1 (L), blood eosinophilic count (x1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The withdrawal of ICS in patients with a low EOS count may be hindered by both patient and provider resistance. In a recent real-life study by Nielsen et al, 96 consecutive patients with COPD had their ICS treatment abruptly withdrawn [44]. Although lasting withdrawal was possible in some patients, more than half resumed ICS irrespective of history of exacerbations and eosinophilic count.…”
Section: Discussionmentioning
confidence: 99%
“…The withdrawal of ICS in patients with a low EOS count may be hindered by both patient and provider resistance. In a recent real-life study by Nielsen et al, 96 consecutive patients with COPD had their ICS treatment abruptly withdrawn [44]. Although lasting withdrawal was possible in some patients, more than half resumed ICS irrespective of history of exacerbations and eosinophilic count.…”
Section: Discussionmentioning
confidence: 99%
“…In two recent real-life studies, Magnussen et al 34 found that discontinuation of ICS was not associated with an increased risk of exacerbation in primary care patients with very few exacerbations, but ICS should not be withdrawn in a subgroup of patients with frequent oral corticosteroid cycles and elevated blood eosinophil counts due to the risk of exacerbations. In a 6-month follow-up study after ICS withdrawal, Nielsen et al 35 found that 60% of patients resumed ICS due to exacerbations. Our results show we were unable to predict the patients who could benefit from the withdrawal or continuation of ICS according to the rate of exacerbations or the eosinophil count.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Obstructive Pulmonary Disease (COPD) is a progressive chronic disease characterized by irreversible, fixed airways obstruction, progressive destruction of lung parenchyma and airways inflammation. 1 Mucus hypersecretion and narrowing of the airways 2 contribute to symptoms including excessive sputum production, dyspnoea and chronic cough 3 punctuated by episodes of acute worsening of symptoms known as exacerbations. 4 The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2023 guidelines recommend that the mainstay of treatment for COPD patients includes long-acting muscarinic antagonists (LAMA) and long-acting beta agonists (LABA).…”
Section: Introductionmentioning
confidence: 99%